Development of Animal-Shaped Dakon Seeds Media to Enhance Early Childhood Cognitive Skills - Komariyah, Kanada; Amelia, Ananda; Meriyati, Meriyati; Jatmiko, Agus (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to: (1) develop animal-shaped dakon seeds media that is feasible for use in cognitive learning; (2) determine the feasibility of the media based on expert validation and user responses; and (3) measure the effectiveness of the media in improving early childhood cognitive abilities. This research is expected to provide an alternative creative learning medium and serve as a solution to enhance early childhood cognition through educational play activities. The study employed the Research and Development (R&D) method with the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The validity test was conducted by material experts, media experts, and early childhood education teachers, followed by small- and large-group trials at PAUD Harapan Bunda and TK Aisyiyah Bustanul Athfal 1. The validation results indicated that the media was feasible, with percentage scores ranging from 88% to 96%. Meanwhile, trial results showed that 92.9% of children at TK Aisyiyah Bustanul Athfal 1 and 83.3% of children at PAUD Harapan Bunda demonstrated improvement. Thus, it can be concluded that animal-shaped dakon seeds media is suitable for use as a learning aid and proven effective in enhancing early childhood cognitive development, while also making the learning process more enjoyable, interactive, and meaningful.